Environmental remediation of the norfloxacin in water by adsorption: advances, current status and prospects (2024)
Antibiotics are considered as the new generation water pollutants as these disturb endocrine systems if water contaminated with antibiotics is consumed. Among many antibiotics norfloxacin is present in various natural water bodies globally. This antibiotic is considered an emerging pollutant due to its low degradation in aquatic animals. Besides, it has many side effects on human vital organs. Therefore, the present article discusses the recent advances in the removal of norfloxacin by adsorption. This article describes the presence of norfloxacin in natural water, consumption, toxicity, various adsorbents for norfloxacin removal, optimization factors for norfloxacin removal, kinetics, thermodynamics, modeling, adsorption mechanism and regeneration of the adsorbents. Adsorption takes place in a monolayer following the Langmuir model. The Pseudo-second order model represents the kinetic data. The adsorption capacity ranged from 0.924 to 1282 mg g−1. In this sense, the parameters such as the NFX concentration added to the adsorbent textural properties exerted a great influence. Besides, the fixed bed-based removal at a large scale is also included. In addition to this, the simulation studies were also discussed to describe the adsorption mechanism. Finally, the research challenges and future perspectives have also been highlighted. This article will be highly useful for academicians, researchers, industry persons, and government authorities for designing future advanced experiments.